Zoo Proverbs as Cultural Artifacts: A Comparative Axiological Study between China and the English-Speaking World (Architecture Image Studies, 2025)
This paper examines the symbolic meaning of zoo proverbs as cultural artefacts through a comparative axiological analysis of Chinese and English-speaking zoo proverbs. As a linguistic item, zoo proverbs, as a metaphorical expression of moral values that use animals as metaphors, represent and support the social and ethical structures of the societies where they originate. The study explores the moral lessons in a sample of proverbs in both cultural situations, revealing the values of the two, i.e., bravery, wisdom and loyalty, and the different forms of their manifestations. The paper uses the axiological approach to comprehend how these proverbs summarise the cultural beliefs about the manners of human conduct, social norms and the natural world. Results are that Chinese proverbs support family, social harmony and collectivism, and the English-speaking proverbs support individualism, personal success and moral complexities. The study makes a contribution to the axiology and comparative cultural studies field, providing information about the application of proverbs in morality education and intergenerational cultural transmission. The results of this research can be applied in informing language and cultural education since they offer educators and students with ample illustrations of the use of animals in language in a metaphorical way to express cultural values. Proverbs have widely been employed in language classes as a way of learning not only vocabulary and grammar, but also the underlying cultures in which they are practised.